2021
DOI: 10.1002/adts.202100113
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Nanomachining Mechanism between Monocrystalline and Polycrystalline Silicon Carbide

Abstract: As an advanced ceramics material, silicon carbide (SiC) is extensively applied in numerous industries. In this study, molecular dynamics method is used to comparatively investigate the nanomachining mechanism between monocrystalline SiC (mono-SiC) and polycrystalline SiC (poly-SiC) ceramics. Four simulations are performed for the two materials with and without ultrasonic vibration-assisted machining (UVAM). The diamond tool is set as a non-rigid body and vibrated along the depth direction with 100 GHz in frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The normal force is always greater than the tangential force; these findings are consistent with previous studies. 3,34 However, regardless of whether the coating thickness is 1.5 nm or 1 nm, the cutting force of Cu coating is always lower than that of other metal coatings when the coating thickness is the same. The tangential force of the uncoated model is about 800 nN greater than that of the 1.5 nm Cu coating and 450 nN greater than that of the 1 nm Cu coating.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The normal force is always greater than the tangential force; these findings are consistent with previous studies. 3,34 However, regardless of whether the coating thickness is 1.5 nm or 1 nm, the cutting force of Cu coating is always lower than that of other metal coatings when the coating thickness is the same. The tangential force of the uncoated model is about 800 nN greater than that of the 1.5 nm Cu coating and 450 nN greater than that of the 1 nm Cu coating.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that stress is an important factor in nano-machining, reflecting the plastic deformation of the workpiece. 3 In this regard, hydrostatic stress, Von Mises stress, tangential stress, and normal stress are widely studied. 46,47 Figures 10 and 11, respectively, show the Von Mises stress nephogram and the hydrostatic stress nephogram for different metal coating thicknesses when the cutting distance is 16 nm.…”
Section: Temperature and Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Goel et al 38 used MD simulation to evaluate the ductile response of single-crystal silicon carbide during nano-cutting. To improve the surface quality after cutting, many scholars have carried out vibration-assisted cutting 39,40 and ion implantation assisted cutting 41 on silicon carbide. While monocrystalline silicon carbide is deeply favored by researchers, polycrystalline silicon carbide is also widely discussed.…”
Section: Introductionmentioning
confidence: 99%
“…While monocrystalline silicon carbide is deeply favored by researchers, polycrystalline silicon carbide is also widely discussed. Liu et al 40 established a comparison model of single-crystal and polycrystalline silicon carbide, and found that single crystal is easier to cause tool wear. Liu et al 17 used the three-dimensional MD simulation method to study the nano-scratching mechanism of polycrystalline silicon carbide.…”
Section: Introductionmentioning
confidence: 99%